Pengaruh Motivasi dan Komunikasi Terhadap Kinerja Karyawan Pada BUMDes Eka Budi Sakti di Desa Seraya, Kabupaten Karangasem - Sujana, I Wayan Agus; Suwendra, I Wayan (Jurnal Pendidikan Ekonomi Undiksha, 2023)
This research aims to determine the partial and simultaneous effects of motivation and communication on staff performance at BUMDes Eka Budi Sakti in Seraya Village. This is an example of a causal study. The population of this research consisted of 38 BUMDes Eka Budi Sakti personnel. The sampling strategy used a saturated sample, in which the whole population served as the study sample. Observation and questionnaires are used during data collection. Multiple linear regression analysis, including the t-test and F-test, is utilized to analyze the data with the assistance of SPSS version 26.0 for Windows. This research indicates that motivation and communication have a favorable and substantial impact on employee performance at BUMDes Eka Budi Sakti in Seraya Village, either partly or concurrently. 64.2% of employee performance at BUMDes Eka Budi Sakti in Seraya Village is impacted by motivation and communication, whereas the remaining 35.8% is influenced by factors outside the scope of this research.